Workshop Penulisan Kamus Dwibahasa Istilah Keislaman Melalui Pembelajaran Berbasis Proyek Bagi Siswa Madrasah Aliyah Negeri 1 Kampar - Marwa, Marwa; Herlinawati, Herlinawati; Syahdan, Syahdan (Universitas Nusantara PGRI Kediri, 2021)
Madrasah Aliyah, which prioritizes the mastery of two foreign languages, both English and Arabic (a language that is closely related to Islamic law) requires the equivalence of knowledge in the two foreign languages, especially in Islamic terms. The Students must be able to communicate in English and be able to become preachers on a global scale. For this reason, the community service team from FKIP Universitas Lancang Kuning needs to carry out a workshop on the project of a bilingual dictionary of Islamic terms through project-based learning for students of MAN 1 Kampar. The team has conducted a workshop via zoom meeting for 70 minutes and continued with intensive discussions via WhatsApp for 6 weeks. The results show the participants can understand the steps of compiling a dictionary well and are expected to finish compiling the projected dictionary. Finally, the team concluded that the training for the project of the Islamic terms bilingual dictionary for students could provide them with knowledge, understanding and ability to compile and complete the dictionary.